International competition and the change of the production matrix - Barrientos Felipa, Pedro (2017)
The exporting commercial projection of a country implies recognizing the importance of trade as well as competition or other supplier countries that seek to supply the same target market. To compete a country must diversify its production matrix, which is why it must increase its production and add new lines of business. A sector that has expectations in Peru is agriculture that is diversifying by the expectations of investors. The proposal is that the State must act in a coordinated manner with all sectors as an agent that allows knowing how much support is needed to be able to compete and the resources that are necessary over time. Participation should favor all agents that participate directly, including the State and small farmers. The competition, the diversification and the importance of the productive agents is what the article seeks to expose.